LINGUISTIC LANDSCAPE ANALYSIS ON COFFEE SHOP SIGNBOARD IN KOTA PROBOLINGGO - Prihatini, Nur Dini; Tjahyadi, Indra; Andayani, Sri (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
This research is about linguistic landscape in Coffee Shop Signboard in Kota Probolinggo. This research is focus on language varieties that are used at coffee shop signboard in Kota Probolinggo and the informational function of the Coffee Shop Signboards in Kota Probolinggo. This research is included in descriptive qualitative method. It is chosen because relevant with objective to the study which is describe the phenomenon by word. This research finds that Indonesian is dominant as cafe’s name. It is because Indonesian is easier to understand than foreign language and local language in spoken and written. English is the second language that is used. There is foreign language namely Portuguese, Spanish, Greek, Indonesian – English, and Indonesian – Javanese. The function of signboard is as identity, promotion media, and area marker of coffee shop.